Comparison of Internal Dosimetry of 18F-PSMA-1007 and 68Ga-PSMA-11-HBED-CC. (16th November 2022) - Sharma, Priya; Watts, Ankit; Singh, Harmandeep
Abstract : Background: Prostate cancer (PCa) is the most common cancer in men worldwide. Targeting prostate-specific membrane antigen (PSMA) using radiopharmaceuticals has shown promising results for PCa imaging as well as theranostics. 68 Ga-based PSMA imaging is limited by production of small quantities by generator, and it has led to quest for cyclotron produced 18 F-based PSMA ligands. In the current study, we evaluated the biodistribution and internal dosimetry of 18 F-PSMA-1007 and compared it with 68 Ga-PSMA-11-HBED-CC. Materials and Methods: A total of 8 patients with histopathologically proven PCa were included in the study, of whom 4 patients underwent 18 F-PSMA-1007, and the other 4 patients underwent 68 Ga-PSMA-11-HBED-CC PET/CT. The biodistribution of both tracers was quantified for different organs by computing SUVs. All the patients underwent 5-point serial imaging to compute equivalent dose to essential organs and whole-body effective dose using OLINDA-based dosimetry. Results: The radiotracer uptake in brain, lacrimal gland, salivary gland, heart, lung, liver, gallbladder, spleen, pancreas, intestine, gluteal muscle, and bone marrow were found to be higher in 18 F-PSMA-1007 PET as compared with 68 Ga PSMA-11 PET. Kidney and urinary bladder showed higher SUV value on 68 Ga-PSMA-11-HBED-CC as compared with 18 F-PSMA-1007. The whole-body effective dose from 18 F-PSMA-1007 (1.46E−02 mSv/MBq) was higher than 68 Ga-PSMA-11-HBED-CC (1.03E−02 mSv/MBq). The highest mean equivalent dose from 18 F-PSMA-1007 was observed in the kidneys (1.48E−01 mGy/MBq), followed by spleen (mean, 1.06E−01 mGy/MBq) and liver (6.80E−02 mGy/MBq), whereas 68 Ga-PSMA-11-HBED-CC equivalent dose was maximum in the kidneys (2.13E−01 mGy/MBq), followed by liver (3.03E−02 mGy/MBq), spleen (2.90E−02 mGy/MBq), adrenals (2.67E−02 mGy/MBq), and urinary bladder (1.89E−02 mGy/MBq). Conclusion: Whole-body effective dose from 18 F-PSMA-1007 is higher compared with 68 Ga-PSMA-11-HBED-CC. 18 F-PSMA-1007 shows lesser urinary bladder clearance compared with 68 Ga-PSMA-11-HBED-CC, which can allow better interpretation of prostatic bed without significant radioactive urine interference. 18 F-PSMA-1007 is a cyclotron-produced alternative to generator-produced 68 Ga-PSMA-11-HBED-CC and can emerge as a good diagnostic surrogate for patients planned for 177 Lu-PSMA-617 therapy.